1996
DOI: 10.1038/bjc.1996.446
|View full text |Cite
|
Sign up to set email alerts
|

High glycolysis in gliomas despite low hexokinase transcription and activity correlated to chromosome 10 loss

Abstract: Summary Loss of chromosome 10 was observed in 10 out of 12 xenografted glioblastomas studied. Chromosome 10 carries the gene coding the hexokinase type I isoenzyme (HK-I), which catalyses the first step of glycolysis, which is essential in brain tissue and glioblastomas. We investigated the relationships between the relative chromosome 10 number, the amount of HK-I mRNA, HK-I activity and its intracellular distribution, and glycolysis-related parameters such as the lactate-pyruvate ratio, lactate dehydrogenase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 31 publications
5
70
1
1
Order By: Relevance
“…Tumors rely more on glycolysis than their normal counterparts (1,30), and defects in the mitochondrial respiratory chain may increase free radical production, resulting in oxidative stress (17,32,35). Consistent with these previous reports, glioblastoma multiformes display a 3-fold increase in glycolysis compared with normal tissue (9) and exhibit defects in respiration at various points in the electron transport chain (10). Our initial experiments confirm and expand on these observations.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Tumors rely more on glycolysis than their normal counterparts (1,30), and defects in the mitochondrial respiratory chain may increase free radical production, resulting in oxidative stress (17,32,35). Consistent with these previous reports, glioblastoma multiformes display a 3-fold increase in glycolysis compared with normal tissue (9) and exhibit defects in respiration at various points in the electron transport chain (10). Our initial experiments confirm and expand on these observations.…”
Section: Discussionsupporting
confidence: 80%
“…High rates of glycolysis may in turn activate hypoxia-inducible factor1a -mediated gene expression (8). Furthermore, glioblastoma multiformes and their normal astrocytic counterparts seem to differ in certain aspects of glucose metabolism; specifically, glioblastoma multiformes exhibit a 3-fold increase in glycolysis (9) and display defects in respiration at various points in the electron transport chain (10). Such reports lend credence to efforts to exploit potential differences in metabolic pathways between glioblastoma multiformes and normal tissues.…”
Section: Introductionmentioning
confidence: 89%
“…Another interesting feature is the putative presence of mitochondrial DNA contained within (and perhaps on the surface of) glioma cell line extracellular vesicles (Guescini, Genedani et al), which has also been seen in murine myoblast vesicles as reported by the same group (Guescini, Guidolin et al) ; this finding runs counter to other groups' findings (Valadi et al 2007) and will likely be somewhat controversial. However, given the high glycolytic capacity of gliomas and the distressed and non-uniform appearance and activities of their mitochondria (Oudard et al 1996;Oudard et al 1997;Ordys et al ;Santandreu et al 2008), relationships between exosomes and mitochondria in cancer cells could potentially be an area of fruitful and energetic study. In the next sections we will discuss the broad range signaling abilities, metabolic effects, and immunological properties of brain tumor exosomes/microvesicles, as well as the exosome-induced migratory and protective phenotypes cells experience upon exposure to exosomes.…”
Section: Brain Tumor Exosomes and Microvesicles: Fat Balls On The Brainmentioning
confidence: 99%
“…Hence, substantial evidence exists showing that respiratory capacity is defective in gliomas. Based on their numerous findings in human glioma cell lines and tissues, the Poupon and Arismendi-Morillo groups suggested that the majority of astrocytomas are incapable of producing adequate amounts of energy through oxidative phosphorylation (Oudard et al, 1995(Oudard et al, , 1996(Oudard et al, , 1997Arismendi-Morillo and Castellano-Ramirez, 2008;ArismendiMorillo, 2009ArismendiMorillo, , 2010. Besides these ultrastructure findings, Renner et al (2010) showed that tumor cells isolated from human GBM could produce ATP in the presence of potassium cyanide.…”
Section: Does the Restricted Ketogenic Diet Represent A Viable Optionmentioning
confidence: 99%
“…These findings in animal models and in brain cancer patients indicate that tumor growth rate and prognosis is dependent to a significant extent on circulating glucose levels. Glucose is the prime fuel for glycolysis, which drives growth of most brain cancer (Oudard et al, 1996(Oudard et al, , 1997Seyfried and Mukherjee, 2005a). As long as circulating glucose levels remain elevated, tumor growth will be difficult to manage.…”
Section: Brain Cancer Energy Metabolism and The Standard Of Care: Rolmentioning
confidence: 99%